Trends in Relative Age Effects of top-level female soccer players: a Japanese study - Matsuda, S.; Ishigaki, H. (Perceptual and Motor Skills, 2023)
We investigated recent trends in relative age effect (RAE) findings of top-level female soccer players in Japan, using data from the 2016 to 2020 seasons. We conducted two main analyses: (a) An examination of RAE for all registered players in the Japan Women`s Soccer League (Nadeshiko League) from 2016 to 2020; and (b) an examination of RAE of newly registered players in the league from 2017 to 2020. In the first analysis, we found a significant difference between the number of players born in Q1 (April-June) versus Q4 (January-March), with the number of players born in Q1 greater and with the ratio between these groups ranging from 1.5 to 1.7. In the second analysis, we found a significant relationship between Q1 and Q4 for the 2017 season alone. However, the Q1/Q4 ratio ranged from 1.4 to 1.9, and the semester ratio of S1 (Q1 + Q2))/S2 (Q3 + Q4) ranged from 1.2 to 1.3, suggesting a birth month bias. Thus, there was a RAE in female soccer players playing recently in Japan`s top-level leagues; and the size of the effect did not change significantly across recent seasons.